Zeitschrift für Kulturwissenschaften (transcript-Verlag, 2007)
Cultural studies is a research perspective characterized by combining manydisciplines. The Zeitschrift für Kulturwissenschaften with its foureditorial departments in Germany, Austria, and Switzerland sees itself as a broad and dynamic forum for this approach. Analyzing current and historic events which - as culture - shape thinking, acting, imagining and demanding; at the same time culture also serves as an analytical frame. Each issue includes academic contributions and a diverse and pointed discussion on a particular subject.